EFFECT OF FVIII CO-ADMINISTRATED WITH IVIG IN IMMUNITY TO FVIII IN HEMOPHILIA A MICE - Afraz, Sajjad (My University, 2016)
Background: Hemophilia A is X-linked recessive congenital bleeding disorder. Exogenous infusion of FVIII is the treatment of choice in hemophilia A patients. However, inhibitor development remains the major problem in management of Hemophilia A. It has been showed that IVIG has immunomodulatory effects and it has been being used in the treatment of several autoimmune and inflammatory disorders. Here, we investigated the effect of co-administration of FVIII with IVIG on the development of inhibitor in naive and previously immunized hemophilia A mice. Methods: Initially, hemophiliac mice were immunized by weekly intraperitoneal injection of human recombinant FVIII (rFVIII). The mice then were treated, either by rFVIII/IVIG co-injection or rFVIII alone. In the other experimental group, naive hemophiliac mice were treated with rFVIII/IVIG co-injection for four weeks followed by injection of either rFVIII or rFVIII/IVIG. Plasma's anti-FVIII Ab titer was measured using ELISA. Results: Weekly injection of rFVIII led to the development of anti-FVIII Ab in all previously untreated mice. Treatment of those immunized mice with rFVIII/IVIG co-injection did not reduce the level of pre-existing Ab. On the other hand, naive mice treated with rFVIII/IVIG co-injection showed significantly less Ab titer compared to the mice received rFVIII alone after 4 weeks (mean Ab titre of 1 compared to 39, in rFVIII/IVIG co-injection and rFVIII groups respectively). Although the rFVIII/IVIG-treated mice developed immune response following the injection of rFVIII alone, Ab titer in those that kept receiving rFVIII/IVIG co-injection remained lower compared to other groups during the whole twelve weeks of the experiment. Conclusions: Co-injection of rFVIII with IVIG decreased the anti-FVIII immune response in previously untreated hemophilia A mice. These findings suggest that IVIG co-administration can be effective in management of hemophilia A patients at risk of inhibitor development.
Keywords: Hemophilia A; FVIII-IVIG co-injection; Inhibitor; ELISA